A decomposition technique of generalized degrees of freedom for mixedmode crack problems. (15th March 2017) - Fan, Huo; Zheng, Hong; Li, Chunguang; He, Siming
Summary: The numerical manifold method (NMM) builds up a unified framework that is used to describe continuous and discontinuous problems; it is an attractive method for simulating a cracking phenomenon. Taking into account the differences between the generalized degrees of freedom of the physical patch and nodal displacement of the element in the NMM, a decomposition technique of generalized degrees of freedom is deduced for mixed mode crack problems. An analytic expression of the energy release rate, which is caused by a virtual crack extension technique, is proposed. The necessity of using a symmetric mesh is demonstrated in detail by analysing an additional error that had previously been overlooked. Because of this necessity, the local mathematical cover refinement is further applied. Finally, four comparison tests are given to illustrate the validity and practicality of the proposed method. The aforementioned aspects are all implemented in the high‐order NMM, so this study can be regarded as the development of the virtual crack extension technique and can also be seen as a prelude to an h‐version high‐order NMM. Copyright © 2017 John Wiley & Sons, Ltd.